2015
DOI: 10.1016/j.humimm.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DRB1 genetic variants with the persistence of atopic dermatitis

Abstract: Atopic dermatitis (AD) is a waxing and waning illness of childhood that is likely caused by interactions between an altered skin barrier and immune dysregulation. The goal of our study was to evaluate the association of DRB1 genetic variants and the persistence of AD using whole exome sequencing and high resolution typing. DRB1 was interrogated based on previous reports that utilized high throughput techniques. We evaluated an ongoing nation-wide long-term cohort of children with AD in which patients are asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…To date, only one small WES study has been reported for eczema, in which exomes of 22 Ethiopian patients with ichthyosis vulgaris and atopic eczema were sequenced; this identified possible disease‐causing variants in FLG and related genes, as well as some novel candidate genes, in a rather heterogeneous pattern of risk . Exome sequencing data have been reported for FLG and related genes , and for the human leukocyte antigen region ; however, larger studies will be required to begin to systemically identify rare variants contributing to atopic eczema. In addition, whole genome sequencing and painstaking functional studies will be required to fully assess the complex contribution of non‐coding genetic variants, which is expected to be substantial .…”
Section: Strategies For Investigationmentioning
confidence: 99%
“…To date, only one small WES study has been reported for eczema, in which exomes of 22 Ethiopian patients with ichthyosis vulgaris and atopic eczema were sequenced; this identified possible disease‐causing variants in FLG and related genes, as well as some novel candidate genes, in a rather heterogeneous pattern of risk . Exome sequencing data have been reported for FLG and related genes , and for the human leukocyte antigen region ; however, larger studies will be required to begin to systemically identify rare variants contributing to atopic eczema. In addition, whole genome sequencing and painstaking functional studies will be required to fully assess the complex contribution of non‐coding genetic variants, which is expected to be substantial .…”
Section: Strategies For Investigationmentioning
confidence: 99%
“…54,55 In the Pediatric Eczema Elective Registry study, HLA-DRB1 was associated with increased prevalence and persistence of AD. 56 Although we report hypomethylation in AHRR, DPP10, and HLA-DRB1, the expected change in protein expression was limited to AHR associated with AHRR. Moreover, there is no overlap between differentially methylated genes and differentially expressed genes.…”
Section: Discussionmentioning
confidence: 59%
“…[ 7 12 ] In fact, individuals with certain human leukocyte antigen (HLA) genotypes, such as HLA-B and HLA-DRB1, are found to have an increased tendency to develop both diseases. [ 42 43 44 45 ] Nonetheless, common susceptibility locus and single nucleotide polymorphisms (SNPs) in HLA genes are yet to be found.…”
Section: Discussionmentioning
confidence: 99%